Prevention of Pediatric Respiratory Syncytial Virus Lower Respiratory Tract Illness: Perspectives for the Next Decade - Aranda, Sofia S.; Polack, Fernando P. (Frontiers in Immunology, 2019)
The landscape of infant bronchiolitis and viral pneumonia may be dramatically altered by preventive interventions against respiratory syncytial virus under evaluation today. Pediatric wards in 2018 worldwide may resemble the old polio wards to future generation pediatricians who may be entirely unfamiliar with the packed emergency rooms, lack of available beds, or emergency situations that all physicians caring for children with RSV experience every year. In this review, we describe and discuss different prevention strategies under evaluation to protect pediatric patients. Then, we outline a number of potential challenges, benefits, and concerns that may result from successful interventions after licensure.